Media for Justice and Healing: The Case of Philippine Comfort Women Survivors - Borromeo, Myrna Elizabeth P. (Review of Women's Studies, 2011)
This essay examines the role played by the media in helping Filipino comfort women survivors find justice and healing. It traces the history of media coverage of comfort women in the Philippines, contextualized against general international media on the issue. It also explores the ways that new media is raising awareness on this issue, arguing that the media have played, and will continue to play, a critical role in keeping the stories of the comfort women alive.